2013
DOI: 10.1016/j.homp.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Stimulative influence of germination and growth of maize seedlings originating from aged seeds by 2,4-D potencies

Abstract: Homeopathic potencies of 2,4-D appear to have a beneficial effect on artificially aged maize seeds: they stimulate growth through better substance conversion from seed rest, and shift the redox capacity towards a reduced environment. Further work is required to determine if this is an useful means of improving maize seed germination and growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…A number of earlier papers have highlighted that freezing results in irreversible damage to maize seed grains [25,26]. The present paper has shown that high values of germinability and germination energy of maize grain with 11.12% moisture after storage under different conditions were consistent with those published by other authors studying germination of maize seeds [27][28][29]. The experimentally obtained results of germinability and germination energy correlated with a moisture content of sowing seed grains have confirmed the appropriacy of the NDSU Extension Service guidelines, which recommend long-term storage of maize seeds under 15% moisture at a temperature range of between −1 • C and 10 • C (30-50F), while grains of 22-30% moisture need drying or can be used as fodder [30].…”
Section: Discussionsupporting
confidence: 91%
“…A number of earlier papers have highlighted that freezing results in irreversible damage to maize seed grains [25,26]. The present paper has shown that high values of germinability and germination energy of maize grain with 11.12% moisture after storage under different conditions were consistent with those published by other authors studying germination of maize seeds [27][28][29]. The experimentally obtained results of germinability and germination energy correlated with a moisture content of sowing seed grains have confirmed the appropriacy of the NDSU Extension Service guidelines, which recommend long-term storage of maize seeds under 15% moisture at a temperature range of between −1 • C and 10 • C (30-50F), while grains of 22-30% moisture need drying or can be used as fodder [30].…”
Section: Discussionsupporting
confidence: 91%
“…All seeds stored under air dry conditions will have suffered a degree of deterioration 11 and seeds in long-term storage will eventually lose their viability due to spontaneous biochemical damage occurring at cellular level 12 , leading to natural seed aging and subsequently limiting crop productivity. Seed priming is a technique that partially hydrates seeds in natural or synthetic compounds under specific environment to a point where germination-related metabolic processes begin, but radicle emergence does not occur 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A sample of 100 seeds were selected and placed inside the germinator for 7 days. Inside the germinator, the distilled water and the temperature enable seed germination to occur (Dragicevic et al, 2013). The germination was calculated as number of seeds that germinated out of the total seeds tested.…”
Section: Germination Testmentioning
confidence: 99%